Text on back, dated February 27, 1931: '... Am 2.März des Jahres 1481 wurde der deutsche Feldhauptmann Franz v. Sickingen ... geboren'
Text on back, dated February 27, 1931: '... Am 2.März des Jahres 1481 wurde der deutsche Feldhauptmann Franz v. Sickingen ... geboren'.